Pengaruh Program Habituasi terhadap Penguatan Karakter Siswa SDN No. 67 Kota Timur Kota Gorontalo - Ridha Fitriani J. Ode Bau; Salma Halidu; Isnanto Isnanto; Gamar Abdullah; Candra Cuga (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Strengthening character at the elementary school (SD) level has a very important role in forming moral and ethical foundations for students. One approach that can be used to strengthen student character is through a habituation program. This research aims to determine the effect of the habituation program on strengthening the character of students at SDN No. 67 East City Gorontalo City. The type of research used is quantitative research with a non-experimental (correlational) research design. The population in this study were all students in grades I-VI of SDN No. 67 East City of Gorontalo, namely 140 people. The sample in this study were students of class IV-VI of SDN No. 67 East City, totaling 62 people. The results of the research show that there is an influence of the habituation program on strengthening the character of students at SDN No. 67 East City, Gorontalo City, meaning that the better the way the program is managed and implemented, the greater the influence it will have on strengthening character. The influence of the habituation program on strengthening students' character reached 38.8%, the remaining 61.2% was influenced by other factors.